(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
In the school population, attentional problems are one of the most frequent causes of failure in learning; sometimes these take the form of a specific deficit and in other cases an attention disorder occurs in comorbidity with a learning disorder. It seems crucial to focus on what peculiar characteristics of attention are involved in basic learning in order to contribute to the diagnostic order and to arrange paths of development. This research aims to verify the weight of the different components of attention involved in the outcomes of the first stages of learning. A total of 69 children (34 males and 35 females, aged 6.4±1.1 years and 7.3±1.2 years respectively) in first grade, participated in the study. The results of the correlational analysis carried out show that there are specific significant relationships between the various components of attention and performance in reading, writing and calculation. In particular, visual attention appears to be the aspect most involved in the initial development of the learning of these three abilities. Factorial analysis shows a single factor involved in the learning of reading, writing and calculation: “Rapid Visual Attention”. The processes identified in the factor are: Selective Attention, Visual Selective Attention, Shifting Focus, Focused Attention, Planning and Inhibition. This factor is characterised by speed in Selective/Sustained Visual Attention and this explains the role of attention in success in reading, writing and calculation in the early stages of school learning. The Rapid Visual Attention Factor contributes to rapidity in reading, speed in writing and numerical knowledge in first grade children, confirming the causal relationship between visual attention and initial learning in this age group. This “Rapid Visual Attention” Factor may be crucial in accounting for the comorbidity between Attention Deficit Hyperactivity Disorder and Learning Disabilities.